Chemical composition of Gariss produced from milk of camels with different watering intervals using some traditional containers in Al-Koma Locality, North Darfur State, Sudan - Hafiz I. I. Osman; El Tahir S. Shuiep; Ibtisam E. M. El Zubeir (Journal of Ethnic Foods, 2024)
Abstract Background The nomadic camels herders utilizing the extensive production system in Sudan depend mainly on fermented milk, locally known as Gariss, as their main stable food for several months during the year. Methods This study was conducted to assess some factors (locations, types of containers used for preparing Gariss and camels watering intervals) affecting the compositional content of Gariss that is commonly prepared by nomadic camel herders. Gariss samples (n-118) were collected during February 2018, from nomadic herders in 4 locations in Al-Koma Locality, North Darfur State, Sudan. Results and discussion The chemical analysis conducted during this study indicated that the mean levels of the total solids, fat, protein and ash content and the pH values of Gariss samples revealed 7.35 ± 0.22%, 2.58 ± 0.08%, 1.86 ± 0.04% and 0.67 ± 0.01% and 3.77 ± 0.03, respectively. The data showed that Gariss prepared in Siin showed the highest total solids (7.7 ± 0.71%), protein (2.02 ± 0.18%), fat (2.60 ± 0.19%) and ash (0.68 ± 0.04%) content, while it revealed the lowest pH value (3.61 ± 0.11). Gariss prepared in plastic containers showed the lowest total solids (7.30 ± 0.23%) and protein (1.48 ± 0.28%). Moreover, Gariss from milk of camels that drink water every 14 days revealed high values for total solids (7.91 ± 0.29%), fat (2.80 ± 0.11%), protein (1.99 ± 0.05%) and pH (3.78 ± 0.04), while it showed the lowest ash (0.67 ± 0.02%) content compared to those made from milk of camels with drinking water frequency of 10 days. Conclusion The study concluded that the compositional content of Gariss was affected by the frequency of water drinking by camels in addition to the containers used for its preparation; as the compositional content of Gariss from Siin showed the best values followed by that stored in Bokhsa. Thus, the study recommends that Siin and Bokhsa should be considered as valuable ethnic containers in keeping camel fermented milk with better compositional content.